The Emerging Role of Telomerase Reverse Transcriptase in Mitochondrial DNA Metabolism - Donna M. Gordon; Janine Hertzog Santos (Journal of Nucleic Acids)
Telomerase is a reverse transcriptase specialized in telomere synthesis. The enzyme is primarily nuclear where it elongates telomeres but recent reports have shown that it also localizes to mitochondria. The function of TERT in mitochondria is largely unknown but the available findings point to a role in mitochondrial DNA metabolism. This paper discusses the available data on mitochondrial telomerase with particular emphasis on its effects upon the organellar DNA.